The effect of increasing blood flow rate on dialysis adequacy in hemodialysis patients - Amini, R.; Borzou, S. R.; Goodarzi, Muhammad Taqi; Zandiha, M.; Gholyaf, M.; Torkaman, B. (Saudi journal of kidney diseases and transplantation, 2009)
Inadequacy of dialysis is one of the determinants of morbidity and mortality in patients undergoing dialysis. The aim of this study was to assess the effect of increasing blood flow rate during hemodialysis (HD) on the adequacy of dialysis. In this study, 42 patients on maintenance HD were assessed. Body weight and blood urea nitrogen (BUN) levels before and after HD sessions were recorded on all the study patients. Volume of ultrafiltration, the duration of dialysis, percentage of filter clearance and flow rate of the dialysate were collected and documented in a checklist. Both Kt / V and urea reduction ratio (URR) were determined at two different blood pump speeds, i.e. 200 and 250 mL / min. During HD, hemodynamic status and vital signs of patients were monitored and controlled. After collecting the necessary data, efficiency of dialysis was calculated using the standard formula. Descriptive and analytical statistics was carried out to analyze the data. Using blood flow rate of 200 mL / min, 16.7% of patients had Kt / V higher than 1.3 and URR higher than 65. On the other hand, with flow rate of 250 mL / min, 26.2% of patients had Kt / V higher than 1.3 and 35.7% of subjects had URR higher than 65. Paired t-test with 95% confidence showed a significant difference in dialysis efficiency between two groups. Our data further confirm that increasing the blood flow rate by 25% is effective in increasing dialysis adequacy in HD patients.